The Reality of the use of teaching aids in the teaching of physics in 7th Grade from the point of view of the teachers of this article. (A Field Study in Lattakia ) - نصور رغداء; خضرو أحمد; خريما ميساء أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study aims to identify the reality of the use of teaching aids in the teaching of physics in 7th Grade from the point of view of the teachers of this articl. The researcher designed a questionnaire consisting of 32 questions. Where the sample of the study consisted of 100 teachers of physics science in the city of Lattakia. The results showed that there is no difference in the statistical significance between the average score of male responses and the average score of female answers on the questionnaire that examines the reality of the use of teaching aids. In addition to the existence of differences of statistical significance in the views of the sample members according to the variable of scientific qualification and experience on the questionnaire that examines the reality of the use of educational aids. And in light of these findings the researcher suggests: Prviding all kinds of teaching aids and teachnology in school; to allow teachers to use them. Holding training sessions for teachers in the use of teaching aids and teaching teachnology.